Cu(II)/TBAI-Catalyzed Esterification of Acid Hydrazides via C(sp3)–H Oxidative Coupling - Liu, Guifeng; Jin, Can; Wu, Guomin (Synlett, 2014)
A Cu2+/TBAI-cocatalyzed allylic ester synthesis was developed, which allows a direct coupling of acid hydrazides and cycloalkanes. This process makes use of commercially available, inexpensive, and abundant starting materials. Based on the extensive experimental data, a plausible radical mechanism was suggested.
Keywords: Cu2+/TBAI cocatalysis; direct coupling; acid hydrazides